2018
DOI: 10.4314/ajcem.v20i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Screening of selected medicinal plants for their antifungal properties

Abstract: Background: The rising incidence of fungal infections has created the need for the next generation of antifungal agents, as many of the currently available ones either have adverse effects, or are not active against emerging or re-emerging fungi, leading to the fast progression of resistant strains. Objectives: This study aims at evaluating the antifungal activities of some medicinal plants used traditionally for treating skin infections in Nigeria. Methods: In vitro antifungal activities of seven indigenous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…These phytochemicals are said to be produced to ward off herbivores and microbial attacks. As such, studies reported by Spampinato and Leonardi [2], Sharanappa and Vidyasagar [15], and Aboh et al, [16] have all demonstrated antimicrobial activities of different plants at varying concentration.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…These phytochemicals are said to be produced to ward off herbivores and microbial attacks. As such, studies reported by Spampinato and Leonardi [2], Sharanappa and Vidyasagar [15], and Aboh et al, [16] have all demonstrated antimicrobial activities of different plants at varying concentration.…”
Section: Introductionmentioning
confidence: 88%
“…They include: Candida albicans, Candida pseudoparapsilosis, Candida parapsilosis, and Candida glabrata. The methods of Aboh et al, [16] was used for the standardization of the test isolates to 0.5 McFarland standards. A colony from a 48 h culture plate was aseptically inoculated into 5 mL of sterile normal saline, followed by adjustment of the turbidity to 0.5 McFarland.…”
Section: Preparation and Standardization Of Candida Speciesmentioning
confidence: 99%